Improving patient safety during insertion of peripheral venous catheters: an observational intervention study - Kampf, Günter; Reise, Gesche; James, Claudia; Gittelbauer, Kirsten; Gosch, Jutta; Alpers, Birgit (German Medical Science GMS Publishing House, 2013)
[english] Background: Peripheral venous catheters are frequently used in hospitalized patients but increase the risk of nosocomial bloodstream infection. Evidence-based guidelines describe specific steps that are known to reduce infection risk. However, the degree of guideline implementation in clinical practice is not known. The aim of this study was to determine the use of specific steps for insertion of peripheral venous catheters in clinical practice and to implement a multimodal intervention aimed at improving both compliance and the optimum order of the steps.Methods: The study was conducted at University Hospital Hamburg. An optimum procedure for inserting a peripheral venous catheter was defined based on three evidence-based guidelines (WHO, CDC, RKI) including five steps with 1A or 1B level of evidence: hand disinfection before patient contact, skin antisepsis of the puncture site, no palpation of treated puncture site, hand disinfection before aseptic procedure, and sterile dressing on the puncture site. A research nurse observed and recorded procedures for peripheral venous catheter insertion for healthcare workers in four different departments (endoscopy, central emergency admissions, pediatrics, and dermatology). A multimodal intervention with 5 elements was established (teaching session, dummy training, e-learning tool, tablet and poster, and direct feedback), followed by a second observation period. During the last observation week, participants evaluated the intervention.Results: In the control period, 207 insertions were observed, and 202 in the intervention period. Compliance improved significantly for four of five steps (e.g., from 11.6% to 57.9% for hand disinfection before patient contact; p<0.001, chi-square test). Compliance with skin antisepsis of the puncture site was high before and after intervention (99.5% before and 99.0% after). Performance of specific steps in the correct order also improved (e.g., from 7.7% to 68.6% when three of five steps were done; p<0.001). The intervention was described as helpful by 46.8% of the participants, as neutral by 46.8%, and as disruptive by 6.4%.Conclusions: A multimodal strategy to improve both compliance with safety steps for peripheral venous catheter insertion and performance of an optimum procedure was effective and was regarded helpful by healthcare workers.